Numerical analysis of FRP-composite-strengthened RC panels with anchorages against blast loads - Mutalib, A.; Hao, Hong (American Society of Civil Engineers, 2011)
Extensive research has been conducted to investigate the blast effects on building structures and the protective design methods using the fiber-reinforced polymer (FRP) strengthening concepts in resisting structural damage and preventing injuries against dynamic explosive impacts. Both numerical and experimental studies have proved the effectiveness of FRP in strengthening structures to resist blast loads. However, problems related to end anchorage, bond length, and premature peeling have been concerns when strengthening structures in flexure or shear using FRP. In this paper, numerical analyses of FRP-composite-strengthened RC walls with or without additional anchors are carried out to examine the structural response under blast loads. The results illustrated that an anchor system is often necessary when using external FRP laminates for strengthening RC walls to prevent premature peeling. This study presents three simulations of RC walls, namely, an unstrengthened RC wall, an FRP-composite-strengthened RC wall with end anchorage, and an FRP-composite-strengthened RC wall with both end anchorage and anchors applied at a minimum spacing across the width and height of the RC wall. Commercial software LS-DYNA is used to carry out the structural response analysis. Numerical results show that anchorage of the FRP sheet may prevent peeling damage and therefore enhances the capacity of the FRP-strengthened RC walls against blast loads. However, anchors result in stress concentration and may cause FRP rupture.